Sharing of tacit knowledge among lecturers in support of remote teaching and learning at University of Limpopo, South Africa - Sekwakwa, Ramokone Mildred (My University, 2023)
Sharing tacit knowledge involves sharing skills and experience in the organisation, so that it may be used for the day-to-day duties. This study examined the sharing of tacit knowledge among lecturers in support of remote teaching and learning at the University of Limpopo (UL). The study investigated the importance, strategies, barriers, management and role of Information, Communication and Technology (ICT) towards sharing tacit knowledge among lecturers at UL. The descriptive research design as well as quantitative and qualitative research approaches were used to conduct this study. The target population of the study was members of the executive management (Faculty Deans and School Directors) and lecturers at UL. The quantitative data from lecturers were collected using questionnaires, while qualitative data from the management were collected using interviews. The total population sampling technique was used to select members of the executive management whereas a stratified random sampling technique was used to select lecturers. The quantitative data were analysed through descriptive analysis, using SPSS software and qualitative data were analysed using thematic data analysis. The key findings from the study revealed that there is little evidence of a reward system to encourage lecturers to share knowledge. The study also found that UL does not have Knowledge Management (KM) policy to guide lecturers on knowledge sharing. The study recommends the introduction of rewards to encourage lecturers to share TK. The findings further revealed that internal politics is a barrier to Tacit Knowledge Sharing (TKS) at UL. The study recommends that the management develop and implement KM policy to guide Knowledge Sharing (KS) among lecturers.
Thesis (M. (Information Studies)) -- University of Limpopo, 2024
Keywords: Tacit knowledge; University of Limpopo; Knowledge sharing; Remote learning; Web-based instruction; Tacit knowledge; Organizational learning